Analysis of conductive olfactory dysfunction using computational fluid dynamics - Asama, Youji; Furutani, Akiko; Fujioka, Masato; Ozawa, Hiroyuki; Takei, Satoshi; Shibata, Shigenobu; Ogawa, Kaoru (PloS one, 2022)
Conductive olfactory dysfunction (COD) is caused by an obstruction in the nasal cavity and is characterized by changeable olfaction. COD can occur even when the olfactory cleft is anatomically normal, and therefore, the cause in these cases remains unclear. Herein, we used computational fluid dynamics to examine olfactory cleft airflow with a retrospective cohort study utilizing the cone beam computed tomography scan data of COD patients. By measuring nasal–nasopharynx pressure at maximum flow, we established a cut-off value at which nasal breathing can be differentiated from combined mouth breathing in COD patients. We found that increased nasal resistance led to mouth breathing and that the velocity and flow rate in the olfactory cleft at maximum flow were significantly reduced in COD patients with nasal breathing only compared to healthy olfactory subjects. In addition, we performed a detailed analysis of common morphological abnormalities associated with concha bullosa. Our study provides novel insights into the causes of COD, and therefore, it has important implications for surgical planning of COD, sleep apnea research, assessment of adenoid hyperplasia in children, and sports respiratory physiology.